2020
DOI: 10.1177/0961203320930098
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective habits in children with systemic lupus erythematosus

Abstract: Background Systemic lupus erythematosus (SLE) is a complex autoimmune disease that can involve multiple organ systems. Exposure to ultraviolet radiation (UVR) can exacerbate pre-existing SLE, and can even induce systemic manifestations. This study aimed to investigate the photoprotective habits of children with SLE and the factors that significantly influence those photoprotective habits. Methods This questionnaire-based cross-sectional study included paediatric SLE patients being treated at the Department of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…As a result, a fingertip unit or teaspoon unit has been recommended [ 23 , 27 ]. We found that at the first assessment, a majority of the patients applied sunscreen less than the recommended amount, which is in line with previous studies in SLE patients [ 7 , 26 ] and in the general population [ 28 , 29 ]. An inadequate amount of applied sunscreen significantly decreases its efficacy [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As a result, a fingertip unit or teaspoon unit has been recommended [ 23 , 27 ]. We found that at the first assessment, a majority of the patients applied sunscreen less than the recommended amount, which is in line with previous studies in SLE patients [ 7 , 26 ] and in the general population [ 28 , 29 ]. An inadequate amount of applied sunscreen significantly decreases its efficacy [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…The rate of sunscreen use is higher compared to the adult studies from Abdul Kadir et. al (52.3%) [ 7 ] and Chanprapaph et al(63.5%) [ 25 ] but is approximately close to another study in children in Thailand (95.8%) [ 26 ]. This may be because Thai families place value on family connections and close parent–child relationships.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As a result, a ngertip unit or teaspoon unit has been recommended. 21,25 We found that at the rst assessment, a majority of the patients applied sunscreen less than the recommended amount, which is in line with previous studies in SLE patients 5,24 and in the general population. 26 , 27 An inadequate amount of applied sunscreen signi cantly decreases its e cacy.…”
Section: Discussionsupporting
confidence: 88%
“…al (52.3%) 5 and Chanprapaph et al (63.5%) 23 but is approximately close to another study in children in Thailand (95.8%). 24 This may be because Thai families place value on family connections and close parent-child relationships. Children tend to be more dependent on parents, especially for health and self-care.…”
Section: Discussionmentioning
confidence: 99%